The Winton M. Blount Postal History Symposia : select papers, 2006-2009 - Winton M. Blount Postal History Symposium; Lera, Thomas M. (Washington, D.C. : Smithsonian Institution Scholarly Press, 2010)
"Rarely do scholars of postal organizations and systems meet and discuss their ideas and research with scholars of philately. In an attempt to bridge this gap, the National Postal Museum and the American Philatelic Society hosted the first Winton M. Blount Postal History symposium on 3-4 November 2006 to bring together these two research groups to discuss postal history. This publication covers the next two symposia. The 2010 theme was "Stamps and the Mail: Images, Icons and Identity." Stamps, as official government documents, can be treated as primary resources designed to convey specific political and esthetic messages. Other topics and themes for the symposium were stamp design's influence on advertising envelopes and bulk mailings, censorship of stamps as propaganda as used on letters, and the role of the Citizens' Stamp Advisory Committee or organizations that generate the designs. The 2011 symposium was held at the American Philatelic Center in conjunction with the United States Stamp Society's annual meeting. The United States Stamp Society is the preeminent organization devoted to the study of U.S. stamps. It is a nonprofit, volunteer-run association of collectors to promote the study of the philatelic output of the Bureau of Engraving and Printing and of postage and revenue stamped paper produced by others for use in the United States and U.S. administered areas."--Publisher's website.
Political economy of postal reform in the Victorian age / Richard R. John -- "Little colored bits of paper" collected in the progressive era / Sheila A. Brennan -- WWI philatelic censuses of East Africa / John Kevin Doyle -- Explorations in the official register; statistical analysis of postmaster compensation data from 19th century New Hampshire / Terence Hines and Thomas Velk -- Zeppelin posts in the 1933 Chicago World's Fair, integrating collector and historian methodologies / Cheryl R. Ganz -- "Food will win the war" motor trucks and the farm-to-table postal delivery program, 1917-1918 / Robert G. Cullen -- Philatelic propaganda, a case study -- border changes in Eastern Europe, 1938-1941 / Robin Gates Elliott -- Picking up the pieces, the aftermath of Hiroshima / Janet Klug -- Postal censorship and military intelligence during World War II / Ann Elizabeth Pfau -- 1895 provisional and bisect postage due stamps, a result of the transfer of stamp production to the BEP? / Harry K. Charles, Jr. -- Sunday mail controversy, postal reform, and mail transportation / Diane DeBlois and Robert Dalton Harris -- "Why is a raven like a writing desk?" post office reform, collectible commodities, and victorian culture / Catherine J. Golden -- America's first carrier service, the U.S. City Despatch Post / Larry Lyons -- U.S. 1847 issues; stamps that changed the system / Harvey Mirsky -- From the pulpit to the post; anti-clericalism and communication in Orizaba, 1857-1867 / Rachel A. Moore -- Cheap postage; a tool for social reform / David L. Straight
Includes bibliographical references.
Also available as PDF.
NLJCols20082021
Keywords: Postal service -- History -- Congresses; Postage stamps -- History -- Congresses; Postage stamps; Postal service; Frim arken -- historia; Government publications; Congresses; Conference papers and proceedings; History; Conference papers and proceedings